Immunogenicity in humans of a transdermal multipeptide melanoma vaccine administered with or without a TLR7 agonist - Craig L Slingluff; Gina R Petroni; Walter C Olson; Kimberly A Chianese-bullock; Donna Deacon; Mark Smolkin; William W Grosh; Max O Meneveau; Kevin T Lynch; Elise P Salerno; Elizabeth Woodson; James W Patterson (Journal for ImmunoTherapy of Cancer)
Background Experimental cancer vaccines are traditionally administered by injection in subcutaneous tissue or muscle, commonly with adjuvants that create chronic inflammatory depots. Injection of melanoma-derived peptides induces T cell responses; however, the depots that form following injection may inhibit optimization of the immune response. In skin, epidermal Langerhans cells (LC) are a dominant source of professional antigen presenting cells. We hypothesized that: (1) applying melanoma-derived peptides topically, in proximity to LC, could be immunogenic and safe, with low vaccine-site toxicity and (2) topical toll-like receptor 7 (TLR7) agonist would increase immunogenicity of the peptide vaccine.Methods Twelve melanoma peptides plus a tetanus helper peptide were combined with granulocyte macrophage colony stimulating factor (GM-CSF) and were administered topically on days 1, 8, and 15, to 28 patients randomized to one of four adjuvant preparations: (1) incomplete Freund’s adjuvant (IFA); (2) IFA plus a TLR7 agonist (imiquimod) administered on days 0, 7, 14; (3) dimethyl sulfoxide (DMSO) or (4) DMSO+ imiquimod administered on day 0, 7, 14. Every 3 weeks thereafter (x 6), the peptides were combined with GM-CSF and were injected into the dermis and subcutis in an emulsion with IFA. Toxicities were recorded and immune responses assayed by ELIspot.Results CD8+ T cell responses to transdermal vaccination in DMSO occurred in 83% of participants in group 3 and 86% in group 4, and responses to vaccination in IFA were observed in 29% of participants in group 1 and 14% in group 2. Overall, 61% of participants had CD4+ T cell immune responses to the tetanus peptide, with large, durable responses in groups 3 and 4. Five of seven participants in group 4 had a severe rash, one that was dose limiting. Ten-year overall survival was 67% and disease-free survival was 44%.Conclusions These data provide proof of principle for immunogenicity in humans of transdermal immunization using peptides in DMSO. Further study is warranted into the pharmacokinetics and immunobiology of TLR agonists as vaccine adjuvants during transcutaneous application. Overall survival is high, supporting further investigation of this immunization approach.